A Comparative Analysis of Curriculum Strategies in Five Countries: Indonesia, Finland, Singapore, Japan, and the United States - Hamiya Bintyelyes; Miss Fatonah Sani; Marhamah Marhamah (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2026)
This study compares curriculum strategies in Indonesia, Finland, Singapore, Japan, and the United States to identify common goals and distinctive approaches in facing global educational challenges. Using a qualitative descriptive method through library research, data were collected from academic journals, policy documents, and official reports. The findings show that all five countries view the curriculum as a strategic tool for developing human resources with 21st-century skills, such as critical thinking, creativity, collaboration, and communication, while also emphasizing character education. Indonesia's curriculum has evolved into the flexible and student-centered Merdeka Curriculum, though challenges remain in teacher readiness and regional disparities. Finland applies a trust-based and holistic approach centered on equality and teacher autonomy. Singapore implements a systematic and adaptive curriculum guided by the vision of "Thinking Schools, Learning Nation." Japan emphasizes stability, discipline, and moral education, while the United States adopts a decentralized and innovative system focused on inclusivity and competency-based learning.